CTIM-15. PRELIMINARY RESULTS OF A PHASE II STUDY OF NIVOLUMAB WITH HYPOFRACTIONATED RE-RADIATION AND BEVACIZUMAB FOR RECURRENT MGMT METHYLATED GLIOBLASTOMA. (9th November 2020) - Grommes, Christian; Mehta, Minesh; Miller, Alexandra; Daras, Mariza; Piotrowski, Anna; Boire, Adrienne; Butler, Brittany; Stone, Jacqueline; Pentsova, Elena; Kotecha, Rupesh; Morrison, Tara; Odia, Yazmin; et al.
Abstract: Standard of standard of care for glioblastoma (GBM) remains unsatisfactory with universal disease recurrence and a median survival of < 2 years. Immune checkpoint inhibitors (ICI) have shown limited single-agent activity in GBM thus far. GBMs with methylated MGMT promoter and no baseline corticosteroid dependence may be most likely to derive benefit from ICI. The combination of ICIs with radiation has shown promising activity in other human cancers. Combining nivolumab and re-RT/bevacizumab in GBM may augment ICI activity through immunogenic effects of radiation, may reduce the risk of radiation necrosis by addition of bevacizumab at the time of radiation, and may reduce the need for corticosteroids. In this multicenter phase II study, nivolumab is combined with re-irradiation and optional concurrent bevacizumab followed by nivolumab in patients with first recurrence of IDH-wildtype and MGMT methylated glioblastoma. Primary objective is to improve 1-year overall survival (OS) from 33 (based on EORTC 26101) to 50%. Nine-three patients are required to show a significant finding with an α of 0.05 and 81% power. Thirteen of 93 patient (14%) have been enrolled with a median age of 59 (range 42–71) with a median KPS of 90 (range 70–90). Treatment has been tolerated well without any grade ≥ 4 toxicities and only one grade 3 (amylase elevation). The most common adverse events were pruritus and hypothyroidism in 3/13 (23%). The median progression-free survival (PFS) is 7 months with a 6months PFS of 55.6%. The 12months OS is 66.7%. Patients with recurrent MGMT methylated, IDH-wildtype glioblastoma tolerate trial treatment with acceptable toxicities. Clinical efficacy in the first patients enrolled shows a promising effect. Enrollment is ongoing.